The gene expression pattern as a tool for assessment of components of microenvironment and response to anti-cancer therapy of prostate tumors - Gerashchenko, G.V.; Chashchina, L.I.; Rynditch, A.V.; Kashuba, V.I. (Доповіді НАН України, 2019)
We have analyzed the putative value of the pattern of relative expression (RE) of several genes that might be involved
in a response to anti-cancer therapy, namely AR, PTEN, COX2, FASN, HMGCR, LDLR, and CTLA4, in samples of
prostate adenoma, adenocarcinoma, and the paired conventional normal tissues. We could propose three subtypes of
adenocarcinomas that show the distinct pattern of expression of the above-mentioned genes, characteristics for (1)
cancer-associated fibroblasts (CAFs), (2) tumor-associated macrophages (TAMs), and (3) markers of immune response.
These groups correlate with the prostate cancer subtypes, that were determined earlier, based on the analysis
of RE of the epithelial-to-mesenchymal cell transition (EMT) genes and prostate cancer-associated genes. Noteworthy,
the highest correlation was found for genes characteristic of CAFs. This emphasizes the importance of the
simultaneous analysis of genes, involved in various intercellular interactions between tumor cells and cells of tumor
microenvironment, in prediction of efficacy of anti-cancer therapy. To confirm the presented data, the additional
studies on a larger cohort of the prostate cancer patients are required. Проаналізoвано потенційні значення діапазонів відносної експресії ряду генів, які можуть бути залучені у
відповідь на протиракову терапію, а саме AR, PTEN, COX2, FASN, HMGCR, LDLR і CTLA4, у зразках аденом,
аденокарцином і парних умовно-нормальних тканин передміхурової залози. Визначено три підтипи аденокарцином, які показують чітку картину експресії досліджуваних генів, які характеризують: 1) пухлино-асоційовані фібробласти; 2) пухлиноасоційовані макрофаги; 3) маркери імунної відповіді. Ці групи корелюють з підтипами раку передміхурової залози, які були визначені раніше на основі аналізу відносної
експресії генів, асоційованих з епітеліально-мезенхімальним переходом, і генів, пов’язаних з раком передміхурової залози. Звертає на себе увагу, що найбільша кореляція була знайдена для цих підтипів раку й
групи генів пухлиноасоційованих фібробластів. Це підкреслює важливість одночасного аналізу генів, залучених до різних міжклітинних взаємодій між клітинами пухлин і клітинами пухлинного мікрооточення,
в прогнозуванні ефективності протиракової терапії. Для підтвердження одержаних даних необхідні додаткові дослідження на більшій вибірці хворих на рак передміхурової залози. Проанализированы потенциальные значения диапазонов относительной экспрессии ряда генов, которые
могут быть вовлечены в ответ на противораковую терапию, а именно AR, PTEN, COX2, FASN, HMGCR,
LDLR и CTLA4, в образцах аденом, аденокарцином и парных условно-нормальных тканей простаты. Определены три подтипа аденокарцином, показывающие четкую картину экспрессии исследуемых генов, которые характеризуют: 1) опухолеассоциированные фибробласты; 2) опухолеассоциированные макрофаги;
3) маркеры имунного ответа. Эти группы коррелируют с подтипами рака простаты, которые были детектированы ранее на основе анализа относительной экспрессии генов, ассоциированных с эпителиально-мезенхимальным переходом, и генов, связанных с раком простаты. Важно отметить, что наибольшая корреляция была найдена для этих подтипов рака и группы генов опухолеассоциированных фибробластов.
Это подчеркивает важность одновременного анализа генов, участвующих в различных межклеточных
взаимодействиях между клетками опухолей и клетками опухолевого микроокружения, в прогнозировании эффективности противораковой терапии. Для подтверждения полученных данных необходимы дополнительные исследования на большей выборке больных раком простаты.